Dissipation of Energy in a Compressible Nematic Microvolume Under Effect of a Temperature Gradient - Izabela Śliwa; Pavel V. Maslennikov; Alex V. Zakharov (Crystals)
We have carried out a numerical study of hydrodynamic processes in the hybrid-aligned channel of a compressible liquid crystal (HACLC) under the effect of a temperature gradient <semantics>∇T</semantics> applied across a liquid crystal film. Calculations based on the classical Leslie–Ericksen theory showed that under the effect of <semantics>∇T</semantics>, the HACLC sample settles down to a stationary flow regime with both horizontal u and vertical w components of velocity <semantics>v</semantics>, and the direction and magnitude of <semantics>v</semantics> are strongly effected by the direction of <semantics>∇T</semantics>. Calculations also showed that the relaxation of the stress tensor components <semantics>σij(z,t)<mspace width="3.33333pt"></mspace>(i,j=x,z)</semantics> in the hybrid-aligned compressible nematic microvolume is determined by the direction and magnitude of the thermomechanical force.